2017
DOI: 10.1038/cdd.2017.114
|View full text |Cite
|
Sign up to set email alerts
|

ASK1 facilitates tumor metastasis through phosphorylation of an ADP receptor P2Y12 in platelets

Abstract: Tumor metastasis is the major cause of deaths in cancer patients and is modulated by intertwined stress-responsive signaling cascades. Here we demonstrate that deletion of stress-responsive apoptosis signal-regulating kinase 1 (Ask1) in platelets results in unstable hemostasis and drastic attenuation of tumor lung metastasis, both of which are attributable to platelet dysfunction. Platelet-specific deletion of Ask1 in mice leads to defects in ADP-dependent platelet aggregation, unstable hemostasis and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…ASK1 inhibition slows the growth of gastric cancer xenografts in mice and Ask1 −/− mice have fewer and smaller tumours than wild-type controls in the N-methyl-N-nitrosourea chemically induced gastric tumourigenesis model [72,113]. Moreover, plateletspecific deletion of ASK1 prevents tumour metastasis in mice that have established lung cancer, induced by the injection of either melanoma or Lewis lung carcinoma cells [69,114]. Thus, it is apparent that ASK1 can function as both a tumour suppressor or tumour promoter, depending on the cellular responses induced by ASK1 modulation.…”
Section: Discussionmentioning
confidence: 99%
“…ASK1 inhibition slows the growth of gastric cancer xenografts in mice and Ask1 −/− mice have fewer and smaller tumours than wild-type controls in the N-methyl-N-nitrosourea chemically induced gastric tumourigenesis model [72,113]. Moreover, plateletspecific deletion of ASK1 prevents tumour metastasis in mice that have established lung cancer, induced by the injection of either melanoma or Lewis lung carcinoma cells [69,114]. Thus, it is apparent that ASK1 can function as both a tumour suppressor or tumour promoter, depending on the cellular responses induced by ASK1 modulation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Also, Kamiyama et al further reported that MEKK5/p38 facilitates tumor metastasis through phosphorylation of the ADP receptor P2Y12 in platelets. 30 Although these 2 studies clearly showed the roles of MEKK5 in platelet activation and thrombus formation, MEKK5-deficient mice with prolonged bleeding times limited its application as a viable antiplatelet target. In this study, we found that another MAP3K family member (MEKK3) is highly expressed in human and mouse platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several platelet agonists trigger the phosphorylation of ASK1 in platelets, correlated with platelet aggregation; the aggregation of platelets from ASK1 −/− mice is defective in response to agonists stimuli. Besides, the platelet ASK1 activates MKKs 3/6 and 4, leading to p38 activation, subsequently phosphorylates the key enzyme cytoplasmic phospholipase A2 (cPLA2) in thromboxane A2 (TxA2) generation, resulting in platelet granule release and thrombus formation(Naik et al, 2017) (Kamiyama et al, 2017). …”
Section: Ask1 In Cardiovascular Diseasesmentioning
confidence: 99%